Non-vesicular Lipid Transport Machinery in Entamoeba histolytica - Das, Koushik; Nozaki, Tomoyoshi (Frontiers in Cellular and Infection Microbiology, 2018)
Eukaryotic cells are organized into separate membrane-bound compartments that have specialized biochemical signature and function. Maintenance and regulation of distinct identity of each compartment is governed by the uneven distribution and intra-cellular movement of two essential biomolecules, lipids, and proteins. Non-vesicular lipid transport mediated by lipid transfer proteins plays a pivotal role in intra-cellular lipid trafficking and homeostasis whereas vesicular transport plays a central role in protein trafficking. Comparative study of lipid transport machinery in protist helps to better understand the pathogenesis and parasitism, and provides insight into eukaryotic evolution. Amebiasis, which is caused by Entamoeba histolytica, is one of the major enteric infections in humans, resulting in 40–100 thousand deaths annually. This protist has undergone remarkable alterations in the content and function of its sub-cellular compartments as well represented by its unique diversification of mitochondrion-related organelle, mitosome. We conducted domain-based search on AmoebaDB coupled with bioinformatics analyses and identified 22 potential lipid transfer protein homologs in E. histolytica, which are grouped into several sub-classes. Such in silico analyses have demonstrated the existence of well-organized lipid transport machinery in this parasite. We summarized and discussed the conservation and unique features of the whole repertoire of lipid transport proteins in E. histolytica.